Verbs and Related Issues - Birner, Betty J. (The Discourse Function of Inversion in English, 1996)
Thus far, I have dealt primarily with the preposed and postposed constituents in an inversion, and have not specifically addressed the status of the remaining element present in every token of the construction-the verb. Inversions can be classed into two major categories: those in which this verb is be (henceforth 'be inversion' (BI)) and those in which it is some other verb (henceforth 'non-foe inversion' (NBI)). These two classes have somewhat different semantic and syntactic profiles, which will be discussed at length below. However, both classes will be seen to share certain pragmatic restrictions on the verb; specifically, I will argue that the verb must contribute no new information to the discourse. After proposing this constraint on verbs in inversion, I will turn to an assessment of an account presented in Birner and Ward 1989 that utilizes a focus-open proposition structure and seems to incorporate this verb constraint, but which is in fact unable to account for the data. Finally, having completed my analysis of the discourse status of each of the constituents in an inversion, I will turn to a brief discussion of the intonational correlates of this information status.